18F-FDG activitiy PET/CT and CA-19.9 levels for the prediction of histopathological features and localization of peri- ampullary tumors - Akcam, Atilgan Tolga; Ülkü, Abdullah; Rencuzoğulları, Ahmet; Parsak, Cem Kaan; Yapar, Zeynep; Doran, Figen; Demiryürek, Haluk; Okoh, Alexis Kofi (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: We sought to investigate the roles of maximum standardized uptake value (SUVmax) and serum carbohydrate antigen 19-9 (CA 19-9) in predicting the histopathological features of periampullary tumors. Materials and Methods: Thirty-four patients with histologically confirmed periampullary tumors were classified into two groups, according to the localizations of their tumors (ampulla Vateri or pancreas). SUVmax was obtained from [(18)F]-fluorodeoxyglucose positron emission tomography computed tomography (18F-FDG PET/CT). SUVmax and CA 19-9 levels were measured and compared with histopathological features of the tumors. Logistic regression was used to assess the significance and independence of predictive factors. Results: 18F-FDG PET/CT SUVmax (<2.5 vs. ≥2.5; p=0.031) and CA 19-9 level (normal vs. elevated; p=0.045) were significantly and independently predictive of the histopathological origin of the tumors (ampulla Vateri vs. pancreas). The ratio of CA 19-9 levels and SUVmax were found to be higher in cases of poorly differentiated tumors and tumors greater than 2 cm in diameter. Conclusion: A surgical approach to treatment may be considered for patients who have both i) an established or suspected diagnosis of periampullary tumors and ii) low SUVmax and CA 19-9 levels.